2019
DOI: 10.1063/1.5064802
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field effect on ion pair dynamics upon bimolecular photoinduced electron transfer in solution

Abstract: The dynamics of the ion pairs produced upon fluorescence quenching of the electron donor 9,10-dimethylanthracene (DMeA) by phthalonitrile have been investigated in acetonitrile and tetrahydrofuran using transient absorption spectroscopy. Charge recombination to both the neutral ground state and the triplet excited state of DMeA is observed in both solvents. The relative efficiency of the triplet recombination pathway decreases substantially in the presence of an external magnetic field. These results were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 56 publications
1
19
0
8
Order By: Relevance
“…Applying external magnetic field can modulate the conversion between the singlet and triplet spin configurations in pair of radicals and change the singlet-to-triplet ratio of pair of radicals (Rodgers et al, 2007). It is thus possible to observe MFEs on the reaction (Frankevich et al, 1996), although the indepth mechanism is not clear so far. Inspired by the polaron pair model for organic magnetoresistance (Hu et al, 2010), we propose that the reaction pathways should be spin-dependent, i.e., the AQH-SDS RPs undergo spin-dependent reaction pathways (pathway A and pathway B) that lead to distinct products (cage-type and escape-type) (Okazaki et al, 2002;Turro and Mattay, 1981).…”
Section: Access Isciencementioning
confidence: 99%
See 1 more Smart Citation
“…Applying external magnetic field can modulate the conversion between the singlet and triplet spin configurations in pair of radicals and change the singlet-to-triplet ratio of pair of radicals (Rodgers et al, 2007). It is thus possible to observe MFEs on the reaction (Frankevich et al, 1996), although the indepth mechanism is not clear so far. Inspired by the polaron pair model for organic magnetoresistance (Hu et al, 2010), we propose that the reaction pathways should be spin-dependent, i.e., the AQH-SDS RPs undergo spin-dependent reaction pathways (pathway A and pathway B) that lead to distinct products (cage-type and escape-type) (Okazaki et al, 2002;Turro and Mattay, 1981).…”
Section: Access Isciencementioning
confidence: 99%
“…In comparison, the signal of escape product could be collected at a longer retention time (~20 min) which is close to that of raw AQ molecules (Figure S5). It was found that these two types of products (cage and escape) had different molar ratios for the reaction occurring with/without magnetic field, and more importantly, the field obviously improves the yield of escape product that is corresponding to the triplet RP intermediate (Feskov et al, 2019).…”
Section: Products Analysis and Temporal Evolution Of Reaction Intermediatesmentioning
confidence: 99%
“…This spin conversion can be slowed down by lifting the degeneracy of the triplet sub-levels with an external magnetic field. Using ps-ns transient absorption, we measured the time evolution of the triplet population arising from triplet recombination and observed a decrease of about 15% of the triplet yield in the presence of a magnetic field [8]. This effect was smaller than expected assuming a conventional description of spin conversion.…”
Section: Intermolecular Photoinduced Electron Transfermentioning
confidence: 79%
“…This effect was smaller than expected assuming a conventional description of spin conversion. However, the Ivanov group was able to reproduce both the time evolution of the triplet population and the magnetic field effect using a diffusion-assisted reaction model with the spin conversion described as a coherent process [8]. This result gives a new insight into the coupling of ion pairs on their way to free ions.…”
Section: Intermolecular Photoinduced Electron Transfermentioning
confidence: 99%
“…Интерес к когерентным эффектам в фотохимии обусловлен также новыми экспериментальными данными о реакциях с участием 9,10-диметилантрацена и 1,3-дицианобензола (фталонитрила) в полярных растворителях [13]. В этих реакциях, в частности, исследовалось влияние среды и постоянного внешнего магнитного поля на кинетику и квантовый выход триплетных продуктов рекомбинации зарядов.…”
Section: Introductionunclassified